Тиритака в V-VI вв. н.э. - Зинько, В.Н.; Зинько, А.В. (Материалы по археологии, истории и этнографии Таврии, 2008)
Результаты археологических исследований Тиритаки позволяют сделать вывод о том, что на всей территории этого боспорского города в V в. н.э. продолжалась довольно активная жизнь. Кварталы, открытые В.Ф. Гайдукевичем в южной и восточной частях города, сохранили регулярную застройку и направление основных улиц. Также и в центральной части города (участок XXVI) нашими раскопками выявлены постройки и улицы, в основе своей повторяющие планировку города первых веков. Basing on archaeological research It can be asserted that Tiritaka in the 5th - 6th centuries AD was rather a large and important settlement of Bosporus Kingdom in the southern part of the coast of the Kerch strait. City blocks with public, housing and household buildings opened in 2002-2007 in the central part of the city by the authors of this article and in the southern and eastern parts of the city excavated earlier by V. F. Gajdukevich testify to it. Firstly discovered large complex for tanning leather should be particularly noted as well as a public building - sanctuary which functioned till the mid-5th century. Later, in the first quarter of the 6th century AD, in the southern part of the city a Christian basilica was built. After catastrophic raids onto Bosporus in the last third of the 6th century, Tiritaka was not abandoned by its population and slow process of extinction of the city went on till the mid-7th century.